Development of A Low-Cost Analyzer for Misalignment Identification Based on Vibration and Current Analysis - Dedi Suryadi; Acraz M Bahrum; Novalio Daratha; Radzi Ambar (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2024)
This paper proposes a low-cost analyzer based on vibration and motor current signature analysis (MCSA) using the Arduino microcontroller. Misalignment identification on induction motors with disc coupling is considered a case study. Several methods for misalignment identification have already been conducted in previous research. However, there are still issues with making the identification more reliable and well-known for further investigation. This paper describes the design and development of an analyzer for misalignment identification that is easy to use and fast utilizing a low-cost Arduino microcontroller. Furthermore, this experimental rig also consists of several additional components such as; an induction motor, shaft, and bearing dan disk coupling. In this paper, misalignment distance variables were set in 0 mm, 0.5 mm, 1 mm, and 1.5 mm, and the motor speed was varied from 500 rpm to 1500 rpm with an increment of 100 rpm. The misalignment characteristic was experimentally achieved using an analyzer with two sensors: an accelerometer for vibration analysis and a current sensor for MCSA. As a result, a low-cost analyzer for misalignment has been successfully developed. The results show that misalignment was explicitly defined by dominant peak frequencies at 3X rpm for vibration analysis and side bands around the main frequency for MCSA. Moreover, side-band frequency increases by increasing the misalignment distance.